MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Maretha Wulandari (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding mathematical concept isone of the important aspects of learning mathematics for students. However, the aspect in class VIII SMP Negeri 2 Pariamanis still low. The observation showed that the studentsare less active in participation and consider learning mathematics as a difficult lesson. One effort to improve students understanding of mathematical concepts is to apply learning models that can facilitate and involve student participation as well as provide opportunities for students to build their own knowledge. The model that can be used is cooperative learning model of Think Talk Write type. This type of research is a quasi experimental research with the design of Static Group Design. The technique is simple random sampling, the used instrument is the final test in the form of essay questions to see the understanding of mathematical concepts of students. The data analysis used is t-test. Based on the analysis of the final test results of students' understanding of mathematical concepts obtained the average of the experimental class students is 74.28 and the control class is 68.87. The result of hypothesis test shows that in real level α = 0,05 obtained p-value = 0,046 it can be concluded that understanding mathematical concept of students learning with cooperative learning model type Think Talk Write is better than understanding mathematical concept of students learning with conventional learning. Keywords - Understanding mathematical concept, Cooperative learning, think talk write, Conventional learning